Optimalisasi Perkembangan Motorik Anak Usia Dini melalui Kegiatan Bermain Edukatif di PAUD Sinar Pelangi Dusun Purwodono Desa Batumarta II - Mepi Triwahyuni; Amelda, Desta; Virgita, Andara; Susanti , Intan; Kurniawan, Rifqi; Sari, Enda Kartika (CV. Ulil Albab Corp, 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student community engagement aimed at applying academic knowledge directly to society. This KKN activity was carried out at PAUD Sinar Pelangi, Purwodono Hamlet, Batumarta II Village, with a focus on optimizing early childhood motor development through educational play activities. Early childhood is a critical period that requires appropriate stimulation to support optimal physical growth and development, particularly in gross and fine motor skills. Based on observations conducted during the KKN program, it was found that the motor development of children at PAUD Sinar Pelangi had not yet been fully optimized due to limited variations of structured educational play activities. Therefore, educational play activities such as drawing, coloring, and pencil sharpening were implemented as stimulation to improve children’s fine motor skills and hand-eye coordination. The implementation method used was direct learning through guided educational play activities, where children actively participated under supervision and assistance. The results of this activity showed positive responses from the children, indicated by increased enthusiasm, creativity, and participation during the learning process. In addition, these activities contributed to improving children’s fine motor skills. It is expected that this program can increase awareness among teachers, parents, and the community regarding the importance of educational play as a means of stimulating early childhood motor development. Furthermore, this activity is hoped to serve as a reference for the continued application of educational play activities in daily learning at PAUD Sinar Pelangi